Influence of Cultivation Conditions on Microalgae Dunaliella Salina Resistance to Lower Temperatures - Chernobai, Nadiia A. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):170.